Where there's a will there's a way: mobile media sharing in urban india - Smyth, Thomas N.; Kumar, Satish; Medhi, Indrani; Toyama, Kentaro; Thies, Indrani Medhi (CHI '10: Proceedings of the 28th international conference on Human factors in computing systems, 2010)
We present the results of a qualitative study of the sharing and consumption of entertainment media on low-cost mobile phones in urban India, a practice which has evolved into a vibrant, informal socio-technical ecosystem. This wide-ranging phenomenon includes end users, mobile phone shops, and content distributors, and exhibits remarkable ingenuity. Even more impressive is the number of obstacles which have been surmounted in its establishment, from the technical (interface complexity, limited Internet access, viruses), to the broader socioeconomic (cost, language, legality, institutional rules, lack of privacy), all seemingly due to a strong desire to be entertained. Our findings carry two implications for projects in HCI seeking to employ technology in service of social and economic development. First, although great attention is paid to the details of UI in many such projects, we find that sufficient user motivation towards a goal turns UI barriers into mere speed bumps. Second, we suggest that needs assessments carry an inherent bias towards what outsiders consider needs, and that identified “needs” may not be as strongly felt as perceived.